Ultrastructural and immunocytochemical evidence of a colonial nervous system in hydroids - Kosevich, Igor A. (Frontiers in Neural Circuits, 2023)
As sister group to all Bilateria, Representatives representatives of the phylum Cnidaria (sea anemones, corals, jellyfishes and hydroids), the basal, group of metazoans possessing a recognisable and well-developed nervous system and, have attracted considerable attention over the years from neurobiologists and Evo-Devo researchers. Despite a long history of nerve nervous system investigation in Cnidaria, predominant number ofmost studies were were performed on unitary organisms. However, most of thethe majority of cnidarians are colonial (modular) organisms with unique specific features of development and functioning.Nevertheless, the data on the nerve nervous system in colonial cnidarians are scantyscarce.Within hydrozoans (Hydrozoa, Cnidaria), a structurally 'simple' nerve nervous system was described for Hydra and zooids of several colonial (modular) species. A mMore complex organisation of nerve nervous system, closely related to the animals' motile mode of life, was was shown for the medusa stage and a few siphonophores. The dDirect evidences of the a colonial nerve nervous system interconnecting zooids of the a hydrozoan colony were was obtained only for two species, while it was stated that in other studied species, the coenosarc lacks nerves. In the present work study, the presence of a nerve nervous system in the coenosarc of three species of colonial hydroids was confirmed based on immunocytochemical and ultrastructural investigations. Confocal scanning laser microscopy revealed a loose system composed of delicate, mostly bipolar, neurons visualized by a mixture of anti-tyrosinated and anti-acetylated α-tubulin antibodies, and anti-RF-amide antibodies. Confocal scanning laser microscopy revealed the loose system composed of delicate mostly bipolar neurons. Only ganglion nerve cells were observed. The neurites were found in the growing stolon tips close to its the tip apex. Ultrastructural data confirm the presence of the neurons in the coenosarc epidermis of all the studied species. The neuron-muscular synapsis are asymmetric. In the coenosarc the neurons and their processes settle on the mesoglea and the muscle processes overlay the nerve cells. Some of the neurites run within the mesoglea. The studied species differ in the density of the nerve system within the coenosarc. The possible role of the colonial nerve nervous system in sessile hydroids remain obscurediscussed.